Analisis Dampak Kebijakan Penyaluran Kredit Kepada Umkm Terhadap Pertumbuhan Pembiayaan Umkm Oleh Perbankan [Policy Impact Analysis of Lending to MSMEs on the Growth of MSMEs Financed by Banks] - Chaerani Nisa (Universitas Pelita Harapan, 2016)
Bank Indonesia launched PBI No. 14/22 in 2012. It regulated that it will be mandatory for all commercial banks to give a minimum of 20% of their total credit to Micro, Small and Medium Enterprise (MSME) by 2018 at the latest. With this regulation, the government expects that there will be a significant rise in credit deployment to the MSME sector. This research study shows that by December 2015 there was no significant growth in credit deployment to MSME. As a contrary, the average credit to the MSME sector between January 2012 and December 2015 was lower than the average credit deployment to MSME between January 2011 and Devember 2012.